A system to register the perception and action processes of tennis and wheelchair tennis players in the return to service on court and laboratory - Reina, R.; Moreno, F. J.; Damas, J. S.; Luis, V.; Sabido, R. (International Journal of Computer Science in Sport, 2002)
It is necessary for a successful performance, so much ability in the perception as a precise movement's perform. For instance, it is important to know how environment indexs establish the relationship between the perceptive information and the response (action) of the athletes. The present system has been developed to collect data about the sport behaviour (perceptive and action processes) of tennis and wheelchair tennis players in the return to service. The system can be applied on court and on laboratory situations, by means of multimedia projection.